Oxidative Stress and Pro-Inflammatory Status in Patients with Non-Alcoholic Fatty Liver Disease - Margalida Monserrat-Mesquida; Magdalena Quetglas-Llabrés; Manuela Abbate; Sofía Montemayor; Catalina M. Mascaró; Miguel Casares; Silvia Tejada; Itziar Abete; Maria Angeles Zulet; Josep A. Tur; J. Alfredo Martínez; Antoni Sureda (MDPI AG, 2020)
Background: Nonalcoholic fatty liver disease (NAFLD) is characterized by excessive fat accumulation, especially triglycerides, in hepatocytes. If the pathology is not properly treated, it can progress to nonalcoholic steatohepatitis (NASH) and continue to fibrosis, cirrhosis or hepatocarcinoma. Objective: The aim of the current research was to identify the plasma biomarkers of liver damage, oxidative stress and inflammation that facilitate the early diagnosis of the disease and control its progression. Methods: Antioxidant and inflammatory biomarkers were measured in the plasma of patients diagnosed with NAFLD (n = 100 adults; 40-60 years old) living in the Balearic Islands, Spain. Patients were classified according to the intrahepatic fat content (IFC) measured by magnetic resonance imaging (MRI). Results: Circulating glucose, glycosylated haemoglobin, triglycerides, low-density lipoprotein-cholesterol, aspartate aminotransferase and alanine aminotransferase were higher in patients with an IFC ≥ 2 of NAFLD in comparison to patients with an IFC of 0 and 1. The plasma levels of catalase, irisin, interleukin-6, malondialdehyde, and cytokeratin 18 were higher in stage ≥2 subjects, whereas the resolvin D1 levels were lower. No differences were observed in xanthine oxidase, myeloperoxidase, protein carbonyl and fibroblast growth factor 21 depending on liver status. Conclusion: The current available data show that the severity of NAFLD is associated with an increase in oxidative stress and proinflammatory status. It may be also useful as diagnostic purpose in clinical practice.